Mechanisms involved in agency attribution and their contributions to normal and abnormal experience of agency - Preston, Catherine E. J. (2008)
Agency attribution is the ability to distinguish between events that occur as a result of our own actions and events that occur as a result of the actions of other people. Previous accounts of agency attribution have been mainly divided into two camps, either explaining agency in terms of high-level conscious processes (Stephens and Graham, 2000) or low-level Comparator Model (CM) processes (Frith et al. 2000). Recently, however, theorists have begun to incorporate these two approaches, but as the bulk of previous experiments fail to specify which aspects of agency are investigated, little empirical evidence exists to inform us about how these different mechanisms interact. The aim of the current thesis was to tease apart these processes by examining high-level self/other judgments and low-level motor responses to actual and perturbed visual feedback of self-generated actions. Results from Chapters 3, 4 and 5 suggest that low-level (CM) agency mechanisms are situated in right hemisphere regions, disruption of which can reduce high-level self-judgments (Chapter 5). Proprioception was also found to negatively inform high-level judgments, as reducing proprioceptive signals increased self-judgments and visual-proprioceptive incongruence increased other judgments (Chapters 6 and 7). In terms of low-level agency mechanisms, however, visual-proprioceptive congruence was found to enhance low-level correction of visual perturbations (Chapter 8). Results from Chapter 8 and Chapter 9 provide evidence for a lack of high-level conscious awareness of low-level motor responses, as participants failed to notice their own low-level corrections (Chapter 8) and as a result failed to recognise their own actions (Chapter 9). Therefore, the current body of research provides evidence for a visual-proprioceptive comparison as an integral component of low-level (CM) agency mechanisms, and that these CM processes do not produce feelings of agency per se, but identify mismatches that inform and are then interpreted by conscious awareness.